Abnormal Reward Processing and Visual Selective Attention: an Event-related Potential Investigation with Remitted Depressed Adults - (:unkn) unknown (My University, 2018)
Feedback, rewarding and non-rewarding, received from the environment can facilitate learning, influence motivation and shape behavior (Skinner, 1963; Thorndike, 1898). Recent research has indicated that reward can also enhance cognitive processes such as visual selective attention (Anderson, Laurent, & Yantis, 2011a; Anderson, Laurent, & Yantis, 2011b; Della Libera, Perlato, & Chelazzi, 2011; Krebs, Boehler, Egner, & Woldorff, 2011). Depression is one of the most common, debilitating, and costly forms of mental illness (Katon, 1996; Kessler et al., 2005; Mathers, Fat, & Boerma, 2008) and has been characterized by reduced responsiveness to reward (Henriques, Glowacki, & Davidson, 1994; Henriques & Davidson, 2000). The current study aimed to investigate the connection between abnormal reward processing and visual selective attention in currently euthymic adults with a history of Major Depressive Disorder (rMDD). Indeed, deficits in reward processing may be a trait-like marker for depression, present even in the absence of significant symptoms. To this end, we measured reward processing capabilities, as captured by the feedback-related negativity (FRN), a medial frontal electrocortical event-related potential component, and visual search performance in both remitted and never-depressed individuals. We found that reward enhanced visual search performance, but failed to replicate the group differences and reward sensitivity findings of a similar previous study (Taubitz, Haworth, & Larson, 2015). We also found no evidence for any relationship between FRN amplitude, depression history, reward sensitivity, anhedonic symptomology and incentivized search performance. We did, however, find that participants in the rMDD group had greater search efficiency than controls on Target Present trials during the Incentivized task as well as higher rates of behavioral avoidance – tentatively suggesting that the improved search efficiency in the rMDD group may be a result of a motivation to avoid negative feedback.
Keywords: Anhedonia; Feedback-Related Negativity; Major Depressive Disorder; Remission; Reward; Visual Selective Attention